2017
DOI: 10.9790/1959-0602094753
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Intra-dialytic Stretching Exercises on Leg Muscle Cramp among Hemodialysis Patients

Abstract: End stage renal disease (ESRD) is a chronic disease needing routine hemodialysis (HD)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…However, there was no difference when compared between the intervention groups. The result of the functional capacity test performed at the end, compared to the initial result, showed that both active and passive stretching improved the functional capacity of the participants, and there was no difference in the control group (15) .…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…However, there was no difference when compared between the intervention groups. The result of the functional capacity test performed at the end, compared to the initial result, showed that both active and passive stretching improved the functional capacity of the participants, and there was no difference in the control group (15) .…”
Section: Discussionmentioning
confidence: 88%
“…The study lasted for 12 weeks, with activities conducted three times a week, and the functional capacity test was performed before and after this period. This test consisted of a 6-minute walk, with the distance covered in meters being quantified (15,16) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic kidney disease, also known as chronic renal failure, is an irreversible and progressive loss of functioning renal tissue that occurs when the remaining kidney mass can no longer maintain the body's internal environment. 1 Renal failure is the result of end stage renal disease when the remaining kidney mass can no longer maintain the body's internal environment. Chronic renal disease can take years to develop.…”
Section: Introductionmentioning
confidence: 99%
“…Exercise significantly reduced the severity and frequency of leg muscular cramps, according to the findings. 8 In 2014, at the Shahrekord and Borujen hospitals, I conducted a study to see how isotonic exercise affected the frequency of muscle cramps. A clinical investigation involving 60 hemodialysis patients was conducted.…”
Section: Introductionmentioning
confidence: 99%